Collective Actors, Common Desires. (September 2015) - Frank, Jason
Honig's essay emphasizes neoliberalism's destruction of a world of public things and addresses how we might respond to the catastrophe of their loss. However, to adequately confront the political dilemmas posed by neoliberalism, we must attend to the simultaneous disappearance of both common desires and collective actors. Honig's examples risk obscuring the political importance of this question.